Dance on the path of life. - Snow, Mitchell; Murguia, Francisco (Americas)
Features Centro Cultural Universitario of the Universidad National Autonoma de Mexico's (UNAM) neoclassical ballet dance company Taller Coreografico and its founder Gloria Contreras. Popularity with Mexican audience; Populist approach; Musical choices; Taller's impact on Mexican dance; Influence of ballet teacher Madame Nelsy Dambre on creation of Taller; Contreras' choreographic vision.